2020
DOI: 10.1136/bmjopen-2019-036585
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of digital communication with automated patient interviews and asynchronous chat in Swedish primary care: a qualitative study

Abstract: ObjectivesTo explore staff experiences of working with a digital communication platform implemented throughout several primary healthcare centres in Sweden.DesignA descriptive qualitative approach using focus group interviews. Qualitative content analysis was used to code, categorise and thematise data.SettingPrimary healthcare centres across Sweden, in both rural and urban settings.ParticipantsA total of three mixed focus groups, comprising 19 general practitioners and nurses with experience using a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 21 publications
5
56
1
Order By: Relevance
“…Focusing on the context of Swedish primary care, three different studies recently found that physicians considered the types of telemedicine evaluated to be suitable for some patients and questions, but not for all. [35][36][37] This compares well to our category "Useful under certain conditions", underlining the need for implementation in cooperation with the profession.…”
Section: Comparison With Other Studiessupporting
confidence: 57%
See 1 more Smart Citation
“…Focusing on the context of Swedish primary care, three different studies recently found that physicians considered the types of telemedicine evaluated to be suitable for some patients and questions, but not for all. [35][36][37] This compares well to our category "Useful under certain conditions", underlining the need for implementation in cooperation with the profession.…”
Section: Comparison With Other Studiessupporting
confidence: 57%
“…Findings include increased efficiency and more precise communication, but also reports of overuse, information overload, and misinterpretations. [33][34][35][36][37] While most papers cover specific tools, PCPs' overall views and experiences of telemedicine have been little studied, and not at all in a Swedish context. Consequently, in 2019, we conducted a web-based survey regarding telemedicine among PCPs in southern Sweden.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…eVisits may also facilitate physicians to better manage emotionally demanding patients [ 37 ], possibly reducing the risk of prescribing antibiotics without proper indications. In addition, eVisits provide a convenient way for physicians to use watchful waiting prior to antibiotic prescription as patients easily can access the chat within 72 hours of a consultation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a risk that the system would lead the physician into a logical conclusion and apparently guideline-coherent decision, increasing the risk of cognitive biases such as confirmation bias, which may not have occurred face-to-face in an office setting. eVisits may also facilitate physicians to better manage emotionally demanding patients [37], possibly reducing the risk of prescribing antibiotics without proper indications. In addition, eVisits provide a convenient way for physicians to use watchful waiting prior to antibiotic prescription as patients easily can access the chat within 72 hours of a consultation.…”
Section: Xsl • Fomentioning
confidence: 99%
“…Such externalities may have been present to different extents among our panel, resulting in markedly variable triage decisions compared with each other and the model. Furthermore, the low agreement between the panel and the model in our study may be due to the fact that variation in human interpretation of text-based cues from automated patient interviewing software data in a primary care setting [26] prevents PCPs from determining urgency as consistently as the model, given access to the same amount of data. It should be noted, however, that in the clinical setting, PCPs would acquire additional data through the eVisit chat before making a triage decision.…”
Section: Discussionmentioning
confidence: 78%